Exosome-mediated repair of spinal cord injury: cellular sources, mechanisms of action, and combined therapeutic strategies - Cha, Zaihong; Li, Yu; Pu, Jianeng; Zhang, Yuansheng; Lu, Qixiong; Huang, Wei; Li, Tao; Lu, Xiaoyang (Frontiers in Neurology, 2025)
Spinal cord injury (SCI) presents a significant clinical challenge due to its complex pathology and limited capacity for self-repair, often resulting in substantial physical dysfunction. Conventional treatments emphasize symptom management, yet usually fail to achieve nerve regeneration and full functional recovery. Recently, Exosomes(Exos) have gained attention as key modulators in biological processes such as immune regulation, intercellular communication, and tissue repair, showing promise in nerve injury and regeneration. This review synthesizes recent research on Exosome-based SCI therapies, including their biological origins, mechanisms, potential applications, and current limitations. Although Exos' research in SCI is nascent, early studies indicate promising safety and efficacy. Future studies are encouraged to delve deeper into Exos preparation, optimization, and delivery to maximize therapeutic effectiveness, potentially advancing SCI treatment options.